Visual-Verbal Information Processing During Passive Reading and Categorization of Words in a Phrase - Natal'ya S. Nuzhina; Petr A. Prodius; Irina V. Mukhina (Northern (Arctic) Federal University, 2024)
The purpose of this study was to identify neurophysiological differences in information processing by the brain during passive reading and semantic categorization of individual words within a phrase. Materials and methods. The research involved 25 natural science students of Nizhny Novgorod universities. In the course of the experiment, the subjects were presented with word combinations consisting of an attribute and a noun on a computer monitor. In the first series of presentations, the task was to classify the attribute (target condition) and read the noun (non-target condition), in the second, to classify the noun and read the attribute. This allowed us to assess the restructuring of information processing when changing the task within a phrase, as well as to compare the processing of the word in the first and second positions in the target and non-target conditions. Using the 21-channel Neuron-Spectrum-4/VPM electroencephalograph (Neurosoft, Russia), event-related potentials (ERPs) obtained during the response to presented stimuli were recorded. Results. No differences were observed in attribute processing between the target and non-target conditions when tasks changed. For nouns, differences were revealed in ERP components between the target and non-target conditions. There was a more pronounced peak of the P200 component, a less pronounced peak of the N400 and a late negative wave of the N700 component during the categorization of nouns compared to their passive reading. Thus, when performing different tasks within a phrase, the brain changes the nature of verbal information processing, which is manifested in strengthening early lexical access, followed by the facilitation of lexico-semantic processing and activation of cognitive control mechanisms at the latest stages during the categorization of the second word in a phrase (noun) compared to its passive reading.